Kajian Urgensi Public Private Partnerships di Kota Bandung - Mary Ismowati (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2016)
Bandung city government's desire to work on various projects with a mechanism of Public Private Partnerships ( PPP ) due to limitations of the government for the city of Bandung well within the capability of funding, human resources , technological capabilities , and so forth . This is done to help realize the " Bandung Champion " . City government 's desire based on the opinion the Government is obliged to fulfill its social responsibility to the community economy , and to ensure that public services can be done to the entire community.The aim in this paper to analyze the cooperation scheme of Public Private Partnerships ( PPP ) what is right for the city government The method used in this paper is a descriptive study with technical literature , ie finding relevant theory reference to the case or the problems found , namely the problem of public private partnership cooperation city government with the private sector in the provision of public services . This type of data is secondary data obtained from the documentation media and internet and also sourced from books and other literature sources that support the discussion in this study.In order for the cooperation of public private partnership city government with the private sector managed a few things that must be considered: this cooperation must be strategically important for both parties , this cooperation are complementary rather than mutually competence , openness to information in both parties , and should this cooperation raises link although the true integration of different cultures . Mutual trust is the main thing. Forms of cooperation of public private partnership with the city government to the private sector in the form of contract maintenance , Leasing ( Lease ) or Contract of Build- Operate- Transfer / BOT or Build Operate and Transfer OwnedIt was concluded that the Public -Private Partnership cooperation is not always a bad connotation and in order to succeed , a lot of terms and conditions must be met . It is intended that the government gets the best results , people also get results commensurate , ie welfare . Thus , the spirit of Public -Private Partnership is to strengthen the government or the public service which is considered inefficient